An electrochemical process for the production of synthetic fuels at low temperatures [Resumo] - Fernandes, Vitor (2015)
Following work exploring the low temperature electrolysis in alkaline media, using graphite consumable anodes, from which syngas was obtained1, laboratory studies have been conducted in acid media pursuing higher efficiency in the production of hydrogen and synthetic fuels. Experiments were conducted in an own designed undivided planar cell with 25 cm2 geometrical area electrodes using a 0.5 M H2SO4 solution with and without Fe(II) additions. Fe2+ oxidizes to Fe3+ at the anode surface. The redox couple Fe3+/ Fe2+ acts as an oxidation mediator not only oxidizing the bulk and detached graphite but also the surface functional groups. The practical experimental potential for graphite oxidation is within the range for the electroxidation of the Fe redox couple giving as a result a 4-fold increase in the amount of produced CO2 at near room temperature, when using 0.025 M FeSO4.